KIAT-KIAT WANITA KARIER DALAM MENDIDIK KEPRIBADIAN ANAK USIA DINI DI KELURAHAN PULAU KAROMAH KOTA PEKANBARU - Rona Muhammad; Jasmienti Jasmienti (KOLONI, 2022)
This research is motivated by the phenomenon that mothers often work outside the home, automatically the time to socialize and educate the child's personality will decrease, even though a mother in educating the child's personality is very important and is a full responsibility, but in reality there are still some mothers in the field. who tries to educate his child's personality on the sidelines of his time like he comes home from work he immediately takes the time to hang out, be close, joke and laugh as well as educate the child's personality in the moral, intellectual, social, and emotional aspects of his child. in the sense that it is not far from educating the child's personality, all that is done by the mother so that her child can get the first education from a good mother figure. Even when they are working their children are entrusted to their husbands or parents, but after coming home from work they take the time to embrace or approach their children to fill the time that their mother has left since she worked in the morning until the afternoon. To discuss the research results, this research method is used which is field research, (field research) with a qualitative descriptive approach. From the research that has been done, it can be concluded that the tips of career women in educating the personality of early childhood in RW 02, Pulau Karomah Village, Pekanbaru City, are good but not optimal. Even though it is not maximal, career women are still trying to educate their children's personality, including by doing general tips and special tips, general tips such as educating children's aqidah, children's worship and children's morals. And special tips like modeling or uswatun hasanah and being firm with their children.  Keyword: Tips, Career Woman, Early Childhood, Personality